The Influence of Narcotics Abuse and Prevention among Adolescents in Indonesia - Pakpahan, Katryn NN; Debora, Debora (CV. Rayyan Dwi Bharata, 2024)
Drug abuse has very bad consequences for teenagers. They often even commit criminal acts that involve fraud, theft, robbery and murder. Factors that contribute to narcotics protection, the legal consequences for teenagers who use them, and the relationship between narcotics protection and other criminal acts are problems that arise. Family, school, and place of residence greatly influence the psychology of teenagers aged twelve to eight fifteen years.For criminal offenses committed by children or teenagers, half the adult sentence.Drug abuse can lead teenagers to actions that violate norms, sometimes even to criminal acts. Therefore, it is very important for teenagers to receive guidance to prevent drug protection which leads to criminal acts.